2005
DOI: 10.1002/art.20955
|View full text |Cite
|
Sign up to set email alerts
|

Reduced tumor necrosis factor signaling in primary human fibroblasts containing a tumor necrosis factor receptor superfamily 1A mutant

Abstract: Objective. Tumor necrosis factor receptorassociated periodic syndrome (TRAPS) is an autoinflammatory syndrome associated with mutations in the gene that encodes tumor necrosis factor receptor superfamily 1A (TNFRSF1A). The purpose of this study was to describe a novel TNFRSF1A mutation (C43S) in a patient with TRAPS and to examine the effects of this TNFRSF1A mutation on tumor necrosis factor ␣ (TNF␣)-induced signaling in a patient-derived primary dermal fibroblast line.Methods. TNFRSF1A shedding from neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…They showed a significant decrease of cell death after TNF stimulation in skin fibroblasts derived from 1 patient with the C43S TNFRSF1A substitution (25). In the present study, resistance to TNF-induced apoptosis and to caspase 8 expression was demonstrated in circulating neutrophils, which represent a cell subset closely related to the systemic inflammation occurring during the disease flares observed in TRAPS patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…They showed a significant decrease of cell death after TNF stimulation in skin fibroblasts derived from 1 patient with the C43S TNFRSF1A substitution (25). In the present study, resistance to TNF-induced apoptosis and to caspase 8 expression was demonstrated in circulating neutrophils, which represent a cell subset closely related to the systemic inflammation occurring during the disease flares observed in TRAPS patients.…”
Section: Discussionsupporting
confidence: 66%
“…The actual relevance of the defect of shedding of TNFR p55 from the leukocyte membrane after cell activation has been challenged by the observation of a large variability of this phenomenon in accordance with the different TNFRSF1A mutations analyzed (5,8,11,25).…”
Section: Discussionmentioning
confidence: 99%
“…In this light, it is intriguing that dermal fibroblasts from TRAPS patients were resistant to TNF-induced apoptosis. 37 This work has identified a common molecular basis for the altered receptor trafficking of TNFR1 mutants in TRAPS. The common theme of structural perturbation, oligomerization, and altered trafficking of all TNFR1 mutants studied here, combined with the fact that no TRAPS-associated TNFR1 mutations that result in loss of TNFR1 protein expression have been identified in TRAPS, suggests that the disease results from more than simple loss of normal TNF binding or reduced secretion of the mutant receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Moreover, recent studies indicate a number of other functional abnormalities in mutant p55 receptors, including altered intracellular trafficking, 30 impaired TNF binding, 30 and a defect in TNFinduced leukocyte apoptosis. 31 Patients with TRAPS generally do not respond to treatment with colchicine, which is highly effective in FMF, and, although they are responsive to high-dose corticosteroids, side effects are often limiting. The recognition of the role of the TNF-pathway has led to the introduction of etanercept, the soluble p75 TNFR:Fc fusion protein, in the treatment of TRAPS.…”
Section: Tnf Receptor-associated Periodic Syndromementioning
confidence: 99%